Megahed’s Magnetic Appliance (MMA) for Cessation of Thumb Sucking Habit - Ahmed Megahed; Alyaa Alaa Eldin (Disease and Health Research: New Insights Vol. 2, 2024)
Management of thumb-sucking habit is being performed by many habit-breaking appliances that are associated with speech, chewing, and esthetic problems due to their bulky metal components. These drawbacks may affect patient compliance and call for a new trial with a different habit-breaking appliance that can efficiently break the habit with better patient acceptance. The case discussed in this chapter has undergone comprehensive diagnosis where diagnostic records were taken (Extra-oral and intra-oral photographs, lateral cephalometric and panoramic radiographs, and study models) along with impression for appliance fabrication. When received from the laboratory, the appliances were disinfected, fitted then cemented and adjusted in the patient’s mouth and thumb. The patient and his parent were enlightened about the advantages of the appliances, which entailed cessation of thumb sucking habit thus allowing tooth eruption and open bite closure, and giving them the instructions at the time of appliance insertion. A questionnaire to test patient compliance was given to the parents every follow-up. Treatment was consummated once the child ended 12 months of follow-up regardless of the fact that it could be achieved. Treatment effects were evaluated by comparing pre and post-treatment records along with the questionnaire answers. The report showed the patient was compliant with the appliance, with a significant increase in overbite and the maxillary inter canine width. This might be the result of cessation of thumb pressure on the palate. It also showed a significant reduction in lower anterior facial height. The maxillary incisors had been uprighted. The interlabial gap greatly reduced after treatment while the nasolabial angle recorded no significant change. It was concluded that the magnetic habit breaker was effective in stopping the habit and helping bite closure due to the appliance’s dual effect and good patient acceptance. The anterior open bite was significantly improved with the correction of the maxillary inter-canine width.